Peningkatan Daya Saing UMKM melalui Optimalisasi Kemasan, Legalitas, dan Pengurusan P-IRT di Desa Kawengen - Farah Chalida Hanoum; Titis Nurina; Rita Meiriyanti; Liyandri Rasbina Tarigan; Tahzha Nadira (Jurnal Kabar Masyarakat, 2026)
This Community Service Program aims to improve the competitiveness of MSMEs in Kawengen Village, East Ungaran, Semarang through optimizing packaging design, strengthening business legality, and assisting with Home Industry Food Permit (P-IRT) processing. The main challenges faced by partners include a lack of understanding of business permits, unattractive and uninformative product packaging, and limited knowledge of food safety standards. The program consisted of observation, outreach, practical training, and intensive mentoring. The materials covered the importance of business legality, P-IRT application procedures, principles of effective and regulatory-compliant packaging design, and the application of brand identity to products. Evaluation included pre- and post-tests, as well as assessments of the packaging designs developed by participants. The program demonstrated a significant increase in participants' understanding of packaging legality and standards, as well as their readiness to process P-IRT. This program has proven effective in strengthening MSME competitiveness by improving product quality, consumer trust, and business professionalism.